2019
DOI: 10.1002/ijgo.12859
|View full text |Cite
|
Sign up to set email alerts
|

A community‐based, cross‐sectional study of hrHPV DNA self‐sampling‐based cervical cancer screening in rural Karnataka, India

Abstract: Objective To examine the feasibility of implementing a high‐risk HPV (hrHPV) DNA‐based screening program for cervical cancer and the prevalence of hrHPV DNA‐positive women in a community setting in rural India. Methods A cross‐sectional study was conducted at the community level in the Hunsur taluk of the Mysore district from January to August 2016. Cervical cancer screening was conducted with self‐collected vaginal samples that were analyzed using the Hybrid Capture 2 (HC2) assay (Qiagen, USA). Results The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Community‐based studies from South India observed that self‐sampling is feasible in rural India . Multicentric community‐based studies are needed to evaluate the utility of self‐collected vaginal samples for cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community‐based studies from South India observed that self‐sampling is feasible in rural India . Multicentric community‐based studies are needed to evaluate the utility of self‐collected vaginal samples for cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based studies from South India observed that selfsampling is feasible in rural India. 14,25 Multicentric community-based studies are needed to evaluate the utility of self-collected vaginal samples for cervical cancer screening. The mindset of the Indian woman is not to expose herself unless it is an absolute necessity, and this barrier is almost never broken by imparting knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been reports of their successful use in Africa, Latin America and in developed countries, there is limited data of their use in India (Lazcano-Ponce et al, 2011;Rees et al, 2018). This is also one of the few studies that examined the usefulness of self-sampled swabs for cervical cancer screening in rural India (A Peedicayil et al, 2016;Adsul et al, 2019). Furthermore, the laboratory assessments of both modes of sample collection revealed high concordance when comparing specimens collected by self-sampling and clinician-collected swabs.…”
Section: Interpretation In Light Of Other Evidencementioning
confidence: 95%
“…Cervical cancer research has resulted in innovative methods to address these barriers. Training community health workers to perform visual inspection of the cervix, educating and motivating women particularly in rural areas to self-collect cervical swabs, and instituting more sensitive detection test such as HPV DNA testing are examples of low-cost approaches to facilitate cancer early detection [36][37][38]. Inherent in these approaches are efforts to pair innovations with implementation science and health system strengthening so the most impactful cancer control interventions can be delivered at scale to diverse populations.…”
Section: Notable Advances In Global Cancer Controlmentioning
confidence: 99%
“…This discipline is characterized by a variety of research designs and methodological approaches, partnerships with key stakeholder groups (e.g., patients, providers, organizations, systems, and/or communities), and the development and testing of ways to effectively and efficiently integrate evidence-based practices, interventions, and policies into routine health settings. Examples of cancer implementation research in global settings include developing protocols to improve adherence to treatment guidelines for tobacco cessation in Vietnam [ 58 ], developing community-based strategies to provide cancer screening hard-to-reach communities in Argentina [ 38 ], and evaluating adoption and acceptability of novel cervical sample collection methods for screening in India [ 37 ]. Considering the variation in health care systems and availability of health delivery personnel, implementation science in LMICs also offers the opportunity to understand innovative quality improvement models and models of integration cancer services into existing disease control programs.…”
Section: Unique Opportunities In Global Cancer Researchmentioning
confidence: 99%